A consensus control strategy for unicycles in the presence of disturbances - Ajorlou, Amir; Asadi, Mohammad Mehdi; Aghdam, Amir G.; Blouin, Stephane (2013 American Control Conference, 2013)
In this paper, a distributed consensus control strategy for a team of unicycle agents subject to disturbance is presented. Disturbances on both the translational and angular velocities are considered. It is assumed that disturbance dynamics are known a priori while their initial conditions are unknown. The norm and the angle of a typical control vector for the consensus of disturbance-free single-integrator agents is used to design the proposed controllers. The control input for each agent consists of two parts. One part which leads to consensus in disturbance-free case, and a second term which compensates for the disturbances. The simulation results confirm the efficacy of the proposed controllers.